2017
DOI: 10.18632/oncotarget.20463
|View full text |Cite
|
Sign up to set email alerts
|

MMP9 polymorphism is associated with susceptibility to non-traumatic osteonecrosis of femoral head in a Chinese Han population

Abstract: Non-traumatic osteonecrosis of femoral head (ONFH) is an orthopedic refractory disease with escalating morbidity in Chinese Han population. In our case-control study, we examined eight previously identified MMP9 single-nucleotide polymorphisms (SNPs) in 585 non-traumatic ONFH patients and 507 healthy individuals from northern China to determine whether these SNPs associated with the risk of developing non-traumatic ONFH. Genetic model and haplotype analyses were used to evaluate the association between SNPs an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…HGF interacts to the unique receptor c-Met to activate the PI3K-Akt signaling pathway [31,32], and MMP-9 production is induced by the receptor activator of NF-B ligand (RANKL), a constituent of the membrane-associated TNF ligand family. Both of these factors stimulate osteoclast generation and lead to pathological bone loss in RA [27], which is one of the factors leading to ONFH [33].It was discovered that blocking the PI3K-Akt pathway can also reduce the expression of MMP9 in RA mice and alleviate joint injury [34,35], which could potentially serve as a therapeutic target for RA-induced ONFH. Furthermore, HGF-transgenic mesenchymal stem cells can improve ONFH recovery and may be a promising drug for ONFH therapy [36].…”
Section: Discussionmentioning
confidence: 99%
“…HGF interacts to the unique receptor c-Met to activate the PI3K-Akt signaling pathway [31,32], and MMP-9 production is induced by the receptor activator of NF-B ligand (RANKL), a constituent of the membrane-associated TNF ligand family. Both of these factors stimulate osteoclast generation and lead to pathological bone loss in RA [27], which is one of the factors leading to ONFH [33].It was discovered that blocking the PI3K-Akt pathway can also reduce the expression of MMP9 in RA mice and alleviate joint injury [34,35], which could potentially serve as a therapeutic target for RA-induced ONFH. Furthermore, HGF-transgenic mesenchymal stem cells can improve ONFH recovery and may be a promising drug for ONFH therapy [36].…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that steroid-induced avascular necrosis of the femoral head is the most common type of non-traumatic osteonecrosis of the femoral head ( 3 ). It is estimated that 75,000-150,000 new cases of ONFH are diagnosed every year in China ( 4 ). Reduced bone mass and trabecular fracture may occur after the third stage of ONFH as a result of cell death in the femoral head ( 5 ).…”
Section: Introductionmentioning
confidence: 99%